MANAJEMEN SEKTOR PUBLIK: PERAN DINAS KOPERASI UMKM KOTA METRO DALAM MENGGUNAKAN APLIKASI SIKP UNTUK KUR - Annisa Erlitsya Marchelina (JURNAL DINAMIKA, 2021)
The problem of Micro, Small and Medium Enterprises (MSMEs) as business actors is the capital used to develop the business. The development of MSMEs is the government's responsibility to empower the community through the KUR program. KUR program issued by the government in 2007. Credit KUR is capital or investment to debtors, business entities or productive business groups through the SIKP application which is used as a means of paying credit subsidy bills. The MSME Cooperative Service helps facilitate, provide training and guidance for the development of MSMEs in Metro City. This research uses literature review, citations and reference articles. The results of the study concluded that the MSME Cooperative Service reached out to the Trade Office, the Tourism Office, and the Agriculture and Livestock Service to upload data to the SIKP application to make it easier for prospective debtors (SME business actors) to get bank channel credit.